Plastic lens

JP2025036115APending Publication Date: 2025-03-14ASAHI KASEI KOGYO KABUSHIKI KAISHA

Patent Information

Application Number
JP2024105554
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-06-28
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、生産性に優れ、耐久性がより向上したプラスチックレンズを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036115000009
    Figure 2025036115000009
  • Figure 2025036115000010
    Figure 2025036115000010
  • Figure 2025036115000001
    Figure 2025036115000001
Patent Text Reader

Abstract

To provide a plastic lens which is excellent in productivity and has improved durability.SOLUTION: A plastic lens includes a lens body, an undercoat layer coating an optical effective surface which is at least one surface of the lens body, and an antireflection layer coating the undercoat layer from a side opposite to the lens body, wherein the lens body contains a heat-resistant acrylic resin, the undercoat layer is composed of a silicon oxide SiOx(1<x<2), a refractive index at a wavelength of 500 nm of the undercoat layer is 1.60 or more and 1.70 or less, and thickness of the undercoat layer is more than 300 nm and less than 1,000 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plastic lens. [Background technology]

[0002] Acrylic resins, typified by polymethyl methacrylate (PMMA), are used as optical materials, etc., from the viewpoints of high transparency, low birefringence, photostability, etc. For example, Patent Document 1 discloses a plastic lens in which an antireflection film is formed on the surface of a PMMA substrate. In recent years, acrylic resins with excellent heat resistance have been developed in response to the need for application of acrylic resins to components of surveillance cameras, vehicle-mounted cameras, and the like, which are used in harsh environments such as high temperature and high humidity and require higher durability than conventional cameras. For example, Patent Document 2 discloses a plastic lens using an acrylic resin with excellent heat resistance as a substrate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-273601 [Patent Document 2] International Publication No. 2023 / 074597 Summary of the Invention [Problem to be solved by the invention]

[0004] It is generally known that the shape accuracy of the film formed on the resin substrate is significantly inferior in wet film forming methods compared to dry film forming methods such as vapor deposition. As a result of the study by the present inventors, it became clear that the plastic lens described in Patent Document 2 cannot be used for applications that require high-level control of the surface shape because the hard coat layer is formed by wet film forming between the substrate made of acrylic resin and the anti-reflection layer. In addition, there is a problem in that the productivity is poor because a hard coat application, drying, and curing process is required between the lens substrate molding process and the anti-reflection layer deposition process. On the other hand, the plastic lens described in Patent Document 1 has an anti-reflection film formed on the surface of the substrate by vacuum deposition, which is a dry film formation method, but the PMMA substrate has low heat resistance, and therefore has the problem of being unable to fully meet the durability required for in-vehicle cameras, etc. In recent years, such stronger durability has been widely required for applications other than in-vehicle cameras, and it is necessary to improve the durability of both the substrate and the anti-reflection film.

[0005] Therefore, an object of the present invention is to provide a plastic lens which is easy to manufacture and has improved durability. [Means for solving the problem]

[0006] That is, the present invention is as follows. [1] A plastic lens comprising a lens body, an undercoat layer covering at least one optically effective surface of the lens body, and an anti-reflection layer covering the undercoat layer from the side opposite to the lens body, The lens body includes a heat-resistant acrylic resin, The undercoat layer is made of silicon oxide, SiO x (1 <x<2)からなり、 The refractive index of the undercoat layer at a wavelength of 500 nm is 1.60 or more and 1.70 or less, The thickness of the undercoat layer is more than 300 nm and less than 1000 nm. A plastic lens characterized by: [2] The plastic lens according to [1], wherein the thickness of the undercoat layer is more than 300 nm and not more than 800 nm. [3] the antireflection layer is formed by alternately laminating high refractive index films made of a high refractive index material and low refractive index films made of a low refractive index material, The high refractive index material is at least one of titanium oxide and zirconium oxide, The plastic lens according to [1] or [2], wherein the low refractive index material is a silicon oxide having a refractive index at a wavelength of 500 nm lower than that of the undercoat layer. [4] The plastic lens according to any one of [1] to [3], wherein the heat-resistant acrylic resin has a glass transition temperature of 116° C. or higher. [5] The heat-resistant acrylic resin contains a structural unit having a ring structure in the structure, the structural unit having a ring structure includes at least one selected from the group consisting of a cyclic imide structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit, and a lactone ring structural unit, The plastic lens according to any one of [1] to [4], wherein the proportion of the structural unit having a ring structure in the heat-resistant acrylic resin is 15% by mass or more. Effect of the Invention

[0007] According to the present invention, it is possible to provide a plastic lens which is excellent in productivity and has improved durability. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of an example of a plastic lens (plano-convex lens) according to the present embodiment, the cross section being parallel to and including an optical axis Z. [Diagram 2] FIG. 2(a) is a schematic diagram (front view) of a typical deposition apparatus having a resistance heating type deposition source, and FIG. 2(b) is a schematic diagram (front view) of a typical deposition apparatus having an electron beam heating type deposition source. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Below, we will explain in detail the form for implementing the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to the following description and can be implemented in various modifications within the scope of its gist. In the following, a structural unit constituting the polymer constituting the heat-resistant acrylic resin contained in the plastic lens of this embodiment will be referred to as a "monomer unit" and / or a "structural unit" containing a plurality of such "monomer units". Furthermore, the constituent material of such a "monomer unit" may be referred to simply as "monomer" without the "unit."

[0010] <Plastic lenses> The plastic lens of the present embodiment may be any of a biconvex lens, a plano-convex lens, a meniscus lens, a biconcave lens, a plano-concave lens, a flat lens, a cylindrical lens, a Fresnel lens, a lenticular lens, a fly's eye lens, a lens array, a microlens array, a prism lens, and the like.

[0011] Hereinafter, the plastic lens of this embodiment will be described with reference to the drawings. FIG. 1 is a schematic diagram showing a cross section of an example of a plastic lens (plano-convex lens) according to the present embodiment, the cross section being parallel to and including an optical axis Z. The plastic lens P of this embodiment includes at least a resin lens body P1, an undercoat layer P2 covering at least one optically effective surface of the lens body (plastic lens substrate) P1, and an antireflection layer P3 covering the undercoat layer P2 from the side opposite to the lens body P1. That is, the plastic lens P of this embodiment has the undercoat layer P2 and the antireflection layer P3 laminated in this order on the optically effective surface of the lens body P1. In addition to the undercoat layer P2 and the antireflection layer P3, the plastic lens P of this embodiment may further include other layers, such as an antifouling layer for making the surface of the plastic lens P less susceptible to dirt, and a gas barrier layer for suppressing the penetration of water vapor into the plastic lens P. In the present disclosure, the optically effective surface means a surface or interface that exerts some optical action such as refraction or reflection on a light ray or light beam incident on the surface. In the plastic lens P in FIG. 1, the optically effective surfaces of the lens body P1 are surface Sa and surface Sb, surface Sa is an aspheric surface with a radius of curvature R, and surface Sb is a flat surface (with a radius of curvature of ∞). The plastic lens P in FIG. 1 is an example in which only the optically effective surface Sa is covered with an undercoat layer P2. In the plastic lens of this embodiment, as shown in FIG. 1, only one of the multiple optically effective surfaces may be covered with the undercoat layer P2 and the anti-reflection layer P3, or two or more optically effective surfaces may be covered with the undercoat layer P2 and the anti-reflection layer P3. In the method of manufacturing such a plastic lens P, as described below, after molding the lens body P1, an undercoat layer forming step of depositing an undercoat layer P2 and an antireflection layer forming step of forming an antireflection layer P3 are performed.

[0012] <Lens body P1> The lens body P1 includes a heat-resistant acrylic resin. The term "heat-resistant acrylic resin" refers to an acrylic resin having heat resistance, and "having heat resistance" means that the Vicat softening temperature measured in accordance with ISO 306 B50 is 110°C or higher. The heat-resistant acrylic resin may be used alone or in combination of two or more kinds.

[0013] [Heat-resistant acrylic resin] From the viewpoint of durability, the heat-resistant acrylic resin contained in the lens body P1 preferably has a glass transition temperature (Tg) measured in accordance with JIS-K7121 of 115° C. or higher, more preferably 116° C. or higher, even more preferably 117° C. or higher, and particularly preferably 118° C. or higher. In addition, taking into consideration the moldability of the lens body P1 and the like, the glass transition temperature Tg is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 160° C. or lower.

[0014] The acrylic resin is a polymer containing, as a monomer component, an ethylenically unsaturated monomer having at least one kind of carboxyl group or carboxylate group, and may be a homopolymer or copolymer of the ethylenically unsaturated monomer, or a copolymer of the ethylenically unsaturated monomer and another monomer copolymerizable with the ethylenically unsaturated monomer. Examples of the ethylenically unsaturated monomer having a carboxyl group or a carboxylate group include methacrylic acid, acrylic acid, methacrylic acid esters, and acrylic acid esters.

[0015] The heat-resistant acrylic resin contained in the lens body P1 preferably has a ring structure in its structure. More specifically, the heat-resistant acrylic resin preferably has a structural unit having a ring structure in its structure, and the structural unit having a ring structure preferably includes at least one structural unit selected from a cyclic imide structural unit, a lactone ring structural unit, an aromatic vinyl structural unit, and an alicyclic vinyl structural unit. The structural unit having a ring structure may be of one type alone or of two or more types in combination.

[0016] The ratio of the structural unit having a ring structure in the heat-resistant acrylic resin is preferably 15% by mass or more, more preferably 16% by mass or more, even more preferably 17% by mass or more, and particularly preferably 18% by mass or more, based on 100% by mass of the heat-resistant acrylic resin. The ratio of the ring structure in the above-mentioned range is preferable from the viewpoints of heat resistance, low birefringence, scratch resistance, and moldability.

[0017] Examples of the cyclic imide structural unit constituting the heat-resistant acrylic resin include a maleimide structural unit and a glutarimide structural unit.

[0018] (Maleimide structural unit) As the maleimide structural unit constituting the heat-resistant acrylic resin, a structural unit represented by the following general formula (1) is preferable. [ka] In the general formula (1), R 1 represents any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, and an aryl group having 6 to 12 carbon atoms, and the alkyl group, alkoxy group, cycloalkyl group, and aryl group may have a substituent on a carbon atom.

[0019] The monomer for forming the maleimide-based structural unit is not particularly limited, and examples thereof include maleimide; N-alkyl group-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, and N-cyclohexylmaleimide; and N-aryl group-substituted maleimides such as N-phenylmaleimide, N-methylphenylmaleimide, N-ethylphenylmaleimide, N-butylphenylmaleimide, N-dimethylphenylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide. From the viewpoints of imparting heat resistance and moist heat resistance, the above-mentioned monomers are preferably N-cyclohexylmaleimide, N-phenylmaleimide, N-methylphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide, and from the viewpoints of availability and imparting heat resistance, more preferably N-cyclohexylmaleimide and N-phenylmaleimide, and even more preferably N-phenylmaleimide. The maleimide structural unit may be one type alone or two or more types in combination.

[0020] From the viewpoints of heat resistance, moldability, optical properties, and color stability, the content of the maleimide structural unit is preferably 0 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 5 to 30 mass%, relative to 100 mass% of the heat-resistant acrylic resin. In the present disclosure, the content of the structural units constituting the heat-resistant acrylic resin can be determined by the method described in the examples below.

[0021] (Glutarimide structural unit) The glutarimide structural unit constituting the heat-resistant acrylic resin may be formed after resin polymerization. As the glutarimide structural unit, a structural unit represented by the following general formula (2) is preferable. [ka] In the general formula (2), R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted, for example, with a hydroxyl group. Also, R 3 represents any one selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and a substituted or unsubstituted aryl group having 6 to 18 carbon atoms. Particularly preferably, R 1 , R 2 , and R 3 are all methyl groups. The glutarimide structural unit may be one type alone or two or more types in combination.

[0022] From the viewpoints of heat resistance, moldability, and optical properties, the content of the glutarimide structural unit is preferably 0 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 5 to 30 mass%, relative to 100 mass% of the heat-resistant acrylic resin.

[0023] The glutarimide structural unit can be obtained by known methods, such as a method of copolymerizing a (meth)acrylic acid ester and / or (meth)acrylic acid, followed by reacting ammonia or an amine with urea or unsubstituted urea at high temperature, a method of reacting a methyl (meth)acrylate-styrene copolymer with ammonia or an amine, or a method of reacting poly(meth)acrylic anhydride with ammonia or an amine. Specifically, the method described in US Pat. No. 4,246,374 to RMKopchik can be mentioned.

[0024] In addition, a glutarimide-based structural unit can also be formed by imidizing an acid anhydride such as maleic anhydride, a half ester of the acid anhydride with a linear or branched alcohol having 1 to 20 carbon atoms, or an α,β-ethylenically unsaturated carboxylic acid.

[0025] Furthermore, another preferred preparation method includes a method in which a (meth)acrylic acid ester and, if necessary, an aromatic vinyl monomer or other vinyl monomers are polymerized, followed by an imidization reaction to obtain a resin containing the glutarimide structural unit. In the imidization reaction step, an imidization agent may be used, and a ring-closing promoter may be added as necessary. Here, the imidization agent may be ammonia or a primary amine. As the primary amine, methylamine, ethylamine, n-propylamine, cyclohexylamine, etc. may be suitably used. The method for carrying out the imidization reaction is not particularly limited, and a conventionally known method can be used, for example, a method using an extruder, a horizontal twin-screw reaction apparatus, or a batch reaction tank. The extruder is not particularly limited, and a single-screw extruder, a twin-screw extruder, or a multi-screw extruder can be preferably used. More preferably, a tandem-type reactive extruder in which two twin-screw extruders are arranged in series can be used.

[0026] In addition to the imidization step, the production of the resin may include an esterification step of treating the carboxyl groups of the resin with an esterifying agent such as dimethyl carbonate, etc. In this case, a catalyst such as trimethylamine, triethylamine, tributylamine, etc. may also be used in combination. The esterification step can be carried out, for example, by using an extruder or a batch reaction tank, in the same manner as in the imidization step. For the purpose of removing excess esterifying agent, by-products such as methanol, or monomers, the apparatus used is preferably equipped with a vent port capable of reducing the pressure to atmospheric pressure or below.

[0027] (Lactone ring structural unit) The lactone ring structural unit constituting the heat-resistant acrylic resin may be formed after resin polymerization. As the lactone ring structural unit, a structural unit represented by the following general formula (3) is preferable. [ka] In the general formula (3), R 1 , R 2 , and R 3 each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms. The organic group may contain an oxygen atom. The lactone ring structural unit may be one type alone or a combination of two or more types.

[0028] From the viewpoints of heat resistance, moldability, and optical properties, the content of the lactone ring structural unit is preferably 0 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 5 to 30 mass%, relative to 100 mass% of the heat-resistant acrylic resin.

[0029] The method for forming the heat-resistant acrylic resin containing a lactone ring structural unit is not particularly limited, but examples thereof include a method in which a monomer having a hydroxyl group on a side chain, for example, a monomer having a structure represented by the following general formula (4) (e.g., 2-(hydroxymethyl)methyl acrylate) is copolymerized with a monomer having an ester group, such as a (meth)acrylic acid ester monomer, and then the resulting copolymer is heat-treated in the presence / absence of a specific catalyst to introduce a lactone ring structure into the polymer. [ka]

[0030] In the general formula (4), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted, for example, with a hydroxyl group. R 2 represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, and the hydrocarbon group may be substituted, for example, with a hydroxyl group. Particularly preferably, R 1 is a hydrogen atom, and R 2 is a methyl group.

[0031] Furthermore, as long as the effects of the present invention can be exhibited, the monomer having the structure represented by the general formula (4) may remain unreacted in the heat-resistant acrylic resin.

[0032] (Aromatic vinyl structural unit) As the aromatic vinyl structural unit constituting the heat-resistant acrylic resin, a structural unit derived from an aromatic vinyl monomer represented by the following general formula (5) is suitably used. [ka] In the general formula (5), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted, for example, with a hydroxyl group. R 2is any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms; R 2 may all be the same group or different groups. 2 They may combine together to form a ring structure. n represents an integer of 0 to 5.

[0033] The monomer for forming the aromatic vinyl structural unit is not particularly limited, but examples thereof include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (α-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene. Among the above, styrene and isopropenylbenzene are preferred, and are effective in providing fluidity and in polymerization conversion. From the viewpoint of reducing unreacted monomers by improving the conversion rate, styrene is more preferred. These may be appropriately selected depending on the properties required for the heat-resistant acrylic resin of this embodiment. The aromatic vinyl structural units described above may be of one type alone or in combination of two or more types.

[0034] From the viewpoints of heat resistance, moldability, and optical properties, the content of the aromatic vinyl structural unit is preferably 0 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 4 to 30 mass%, relative to 100 mass% of the heat-resistant acrylic resin.

[0035] (alicyclic vinyl structural unit) The alicyclic vinyl structural unit constituting the heat-resistant acrylic resin may be formed after resin polymerization. As the alicyclic vinyl structural unit, a structural unit represented by the following general formula (6) is preferably used. [ka] In the general formula (6), R1 to R3 each independently represent any one of a hydrogen atom, a chain hydrocarbon group, a halogen atom, an alkoxy group, a hydroxy group, an ether group, an ester group, a cyano group, an amide group, an imide group, a silyl group, and a chain hydrocarbon group substituted with a polar group (a halogen atom, an alkoxy group, a hydroxy group, an ether group, an ester group, a cyano group, an amide group, an imide group, or a silyl group). Among them, a hydrogen atom or a chain hydrocarbon group having 1 to 6 carbon atoms is preferable because of its excellent heat resistance and low water absorption. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the chain hydrocarbon group substituted with a polar group include a halogenated alkyl group having 1 to 20 carbon atoms, preferably 1 to 10, and more preferably 1 to 6 carbon atoms. Examples of the chain hydrocarbon group include an alkyl group having 1 to 20 carbon atoms, preferably 1 to 10, and more preferably 1 to 6 carbon atoms; and an alkenyl group having 2 to 20 carbon atoms, preferably 2 to 10, and more preferably 2 to 6 carbon atoms. X in the general formula (6) represents an alicyclic hydrocarbon group, and the number of carbon atoms constituting the alicyclic hydrocarbon group is usually 4 to 20, preferably 4 to 10, and more preferably 5 to 7. By setting the number of carbon atoms constituting the alicyclic structure within this range, birefringence can be reduced. In addition, the alicyclic structure is not limited to a monocyclic structure, and may be a polycyclic structure such as a norbornane ring or a dicyclohexane ring. The alicyclic hydrocarbon group may have a carbon-carbon unsaturated bond, but the content of the carbon-carbon unsaturated bond is 10% or less, preferably 5% or less, more preferably 3% or less of the total carbon-carbon bonds. By making the carbon-carbon unsaturated bond of the alicyclic hydrocarbon group within this range, transparency and heat resistance are improved. In addition, any of hydrogen atoms, hydrocarbon groups, halogen atoms, alkoxy groups, hydroxy groups, ether groups, ester groups, cyano groups, amide groups, imide groups, silyl groups, and chain hydrocarbon groups substituted with polar groups (halogen atoms, alkoxy groups, hydroxy groups, ether groups, ester groups, cyano groups, amide groups, imide groups, or silyl groups) may be bonded to the carbon constituting the alicyclic hydrocarbon group, and among them, hydrogen atoms or chain hydrocarbon groups having 1 to 6 carbon atoms are preferred in terms of heat resistance and low water absorption.

[0036] Among the structural units represented by general formula (6), the structural unit represented by the following general formula (7) is excellent in heat resistance and low water absorbency. [ka] In general formula (7), Ra, Rb, Rc, and Rd each independently represent a hydrogen atom or a lower chain hydrocarbon group, and a hydrogen atom or a lower alkyl group having 1 to 6 carbon atoms is preferred because of its excellent heat resistance and low water absorption. The above-mentioned alicyclic vinyl structural units may be used alone or in combination of two or more kinds.

[0037] The method for forming the heat-resistant acrylic resin containing an alicyclic vinyl structural unit is not particularly limited, and examples thereof include (1) a method of copolymerizing an aromatic vinyl compound with other monomers containing (meth)acrylic acid or (meth)acrylic acid esters, and hydrogenating the carbon-carbon unsaturated bonds in the main chain and aromatic ring, and (2) a method of copolymerizing an alicyclic vinyl compound with other monomers containing (meth)acrylic acid or (meth)acrylic acid esters, and hydrogenating them as necessary. The method (1) is preferred because it can more efficiently obtain an alicyclic hydrocarbon copolymer. The aromatic vinyl compound used in the above method (1) is not particularly limited, but examples thereof include styrene, α-methylstyrene, α-ethylstyrene, α-propylstyrene, α-isopropylstyrene, α-t-butylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, 5-t-butyl-2-methylstyrene, monochlorostyrene, dichlorostyrene, monofluorostyrene, 4-phenylstyrene, and the like. Among these, styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, and the like are preferred. The alicyclic vinyl compound used in the above method (2) is not particularly limited, but examples thereof include cyclobutylethylene, cyclopentylethylene, cyclohexylethylene (vinylcyclohexane), cycloheptylethylene, cyclooctylethylene, norbornylethylene, dicyclohexylethylene, α-methylcyclohexylethylene, α-t-butylcyclohexylethylene, cyclopentenylethylene, cyclohexenylethylene, cycloheptenylethylene, cyclooctenylethylene, cyclodekenylethylene, norbornenylethylene, α-methylcyclohexenylethylene, and α-t-butylcyclohexenylethylene. Of these, cyclohexylethylene (vinylcyclohexane) is preferred.

[0038] From the viewpoints of heat resistance, moldability, and optical properties, the content of the alicyclic vinyl structural unit is preferably 0 to 80 mass%, more preferably 2 to 60 mass%, and even more preferably 5 to 40 mass%, relative to 100 mass% of the heat-resistant acrylic resin.

[0039] [Method of manufacturing heat-resistant acrylic resin] The method for producing the heat-resistant acrylic resin is not particularly limited as long as the above-mentioned heat-resistant acrylic resin can be obtained, and a conventionally known method can be used.For example, the heat-resistant acrylic resin can be produced by bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, or emulsion polymerization using each monomer for forming each of the above-mentioned structural units.For producing the heat-resistant acrylic resin, preferably, bulk polymerization or solution polymerization is used, and more preferably, solution polymerization is used. The heat-resistant acrylic resin may be produced either continuously or batchwise. In the method for producing the heat-resistant acrylic resin, it is preferable to polymerize the monomers by radical polymerization. In the method for producing the heat-resistant acrylic resin, a known polymerization initiator, chain transfer agent, etc. may be used as necessary.

[0040] [Additives] The lens body P1 is not particularly limited as long as it can exhibit the effects of the present invention, and may contain various additives. The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, lubricants, other thermoplastic resins, softeners / plasticizers such as paraffinic process oil, naphthenic process oil, aromatic process oil, paraffin, organic polysiloxane, and mineral oil, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, compatibilizers, dispersants, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites, and phosphate esters, other additives, and mixtures thereof. The method for kneading the heat-resistant acrylic resin and the additives is not particularly limited, and examples thereof include a method for kneading using a kneader such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. Among these, kneading using an extruder is preferred from the viewpoint of productivity. It is preferable to provide the extruder with a vent port in order to reduce volatile content. The kneading temperature may be in accordance with the preferred processing temperature of the heat-resistant acrylic resin and other thermoplastic resins added as additives, and is generally 140 to 350°C, preferably 180 to 300°C.

[0041] From the viewpoints of ease of molding and mechanical strength, the resin composition containing a heat-resistant acrylic resin and optional additives preferably has a weight-average molecular weight (Mw) of 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 70,000 to 200,000. If the weight-average molecular weight (Mw) is within the above range, the lens body P1 tends to have a good balance between moldability and mechanical strength. From the viewpoints of ease of molding, mechanical strength, and solvent resistance, the resin composition containing the heat-resistant acrylic resin and optional additives preferably has a molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of 1.25 to 3.00, more preferably 1.50 to 2.75, and even more preferably 1.75 to 2.50. When the molecular weight distribution (Mw / Mn) is within the above range, the lens body P1 tends to have a good balance of moldability, mechanical strength, and solvent resistance. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the resin composition can be measured by gel permeation chromatography (GPC), specifically, by the method described in the examples below.

[0042] The lens body P1 is formed by molding a resin composition containing a heat-resistant acrylic resin and, optionally, an additive. The lens body P1 can be manufactured by a molding method such as injection molding, compression molding, extrusion molding, blow molding, cast molding, etc. Also, a desired shape can be obtained by cutting a resin block. Among these, injection molding is preferred from the viewpoint of productivity. The injection molding method and the injection molding machine are not particularly limited, and any conventionally known injection molding method and injection molding machine can be used.

[0043] Typically, injection molding consists of (1) an injection process in which resin is melted and the molten resin is filled into the cavity of a temperature-controlled mold; (2) a pressure holding process in which pressure is applied inside the cavity until the gate is sealed, and an amount of resin is injected equivalent to the amount of molten resin filled in the injection process that comes into contact with the mold and cools and shrinks; (3) a cooling process in which the molded product is held until the resin has cooled after the pressure holding process is released; and (4) the mold is opened and the cooled molded product is removed.

[0044] In this case, the molding temperature is preferably in the range of Tg+100°C to Tg+180°C, and more preferably in the range of Tg+110°C to Tg+160°C, based on the glass transition temperature (Tg) of the resin composition. Here, the molding temperature refers to the cylinder setting temperature of the injection molding machine. The higher the molding temperature, the better the shape transferability of the lens body P1 that can be obtained, but since high temperatures promote coloring due to thermal degradation during retention in the molding machine, the molding temperature should be selected appropriately. The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-10°C, based on the glass transition temperature (Tg) of the resin composition.

[0045] The injection speed can be appropriately selected depending on the thickness and dimensions of the lens body P1 to be obtained, and can be appropriately selected, for example, from the range of 2 to 1000 mm / sec. The pressure for maintaining the pressure can be appropriately selected depending on the shape of the lens body P1 to be obtained, and can be appropriately selected within the range of, for example, 30 to 150 MPa. The pressure for holding the pressure referred to here is the pressure maintained by a screw for further feeding the molten resin from the gate after the molten resin has been filled.

[0046] In addition, an annealing process may be performed to relieve residual stress caused by injection molding and reduce the phase difference of the lens body P1. The annealing temperature is preferably in the range of Tg-50°C to Tg, and more preferably in the range of Tg-30°C to Tg-10°C, based on the glass transition temperature (Tg) of the resin composition. may be used.

[0047] <Undercoat layer> In the plastic lens P of the present embodiment, the undercoat layer P2 is a layer that covers at least one optical effective surface of the lens body P1. The undercoat layer P2 enhances the adhesion between the lens body (plastic lens substrate) P1 and the antireflection layer P3, and suppresses the generation of cracks in the antireflection layer P3 in a high-temperature environment or a high-temperature and high-humidity environment. Therefore, the plastic lens P of the present embodiment is a lens with excellent durability.

[0048] The undercoat layer P2 is composed of silicon oxide SiO x (1 < x < 2). As will be described later, for example, when forming a film by physical vapor deposition using SiO as a material, the composition of the undercoat layer P2 can be made silicon oxide SiO x (1 < x < 2) by forming the film while oxidizing the deposition material in an oxygen atmosphere. Generally, in a film-formed product in which an antireflection layer made of a metal oxide is formed on a resin substrate, when a damp heat test is performed, due to the difference in the linear expansion coefficient and water absorption rate between the resin substrate and the antireflection layer, the antireflection layer cannot follow the expansion of the resin substrate, and cracks occur. However, in the plastic lens P of the present embodiment, since the undercoat layer P2 composed of silicon oxide SiO x (1 < x < 2) is provided between the lens body P1 and the antireflection layer P3 as a buffer layer, the occurrence of cracks is suppressed.

[0049] The refractive index of the undercoat layer P2 at a wavelength of 500 nm is preferably 1.60 or more, more preferably 1.61 or more, and even more preferably 1.62 or more. Also, the refractive index of the undercoat layer P2 is preferably 1.70 or less, more preferably 1.68 or less, and even more preferably 1.66 or less. When the refractive index is within this range, a high suppression effect on crack generation after the damp heat test is exhibited. The refractive index of the undercoat layer P2 is silicon oxide SiO xIt can be controlled by adjusting the composition of (1 < x < 2). For example, when forming the undercoat layer P2 by vacuum evaporation described later, increasing the oxygen partial pressure (increasing the oxygen introduction amount) makes the composition closer to SiO2 and the refractive index lower, while decreasing the oxygen partial pressure (decreasing the oxygen introduction amount) makes the composition closer to SiO and the refractive index higher. The refractive index of the undercoat layer P2 can be measured by the method described in the examples below.

[0050] The thickness (film thickness) of the undercoat layer P2 is preferably more than 300 nm, more preferably 305 nm or more, still more preferably 310 nm or more, even more preferably 315 nm or more, and particularly preferably 320 nm or more. Also, it is preferably less than 1000 nm, more preferably 900 nm or less, still more preferably 800 nm or less, even more preferably 700 nm or less, and particularly preferably 650 nm or less. When the thickness (film thickness) of the undercoat layer P2 is within this range, as described below, when the antireflection layer P3 is formed by vacuum evaporation using a vapor deposition apparatus having an electron beam heating type vapor deposition source, it is possible to prevent the reflected electrons from reaching the surface of the lens body P1. Therefore, it is possible to prevent embrittlement of the lens body P1 due to the reflected electrons and a decrease in the adhesion between the antireflection layer P3 and the lens body P1 due to the embrittlement of the lens body P1. Also, the generation of cracks after the damp heat test can be suppressed. The thickness (film thickness) of the undercoat layer P2 can be determined, for example, by direct observation of the cross section with an electron microscope, ellipsometry, or spectroscopic reflectometry, and specifically, by the method described in the examples below.

[0051] The undercoat layer P2 can be formed by the vacuum evaporation method. The vacuum evaporation method is a method of heating a vapor deposition material in a vacuum chamber to vaporize or sublime it and depositing it on the surface of a substrate placed at a distant position in the chamber to form a thin film. The deposition apparatus used in the vacuum deposition method has a chamber and a deposition source provided in the chamber, and a substrate on which a film is to be formed is held in the chamber. As the deposition source, for example, a resistance heating type deposition source or an electron beam heating type deposition source is used. A schematic configuration diagram of a representative deposition apparatus is shown in FIG. 2. FIG. 2(a) is an example of a deposition apparatus having a resistance heating type deposition source, and FIG. 2(b) is an example of a deposition apparatus having an electron beam heating type deposition source (electron gun). Although not shown in the figure, a deposition apparatus equipped with both a resistance heating type deposition source and an electron beam heating type deposition source can also be used.

[0052] In the deposition apparatus 11 in FIG. 2(a), 12 denotes a chamber, 13 denotes a resistance heating power supply, 14 denotes an evaporation dome, 15 denotes a boat, and 16 denotes a shutter. The resistance heating power supply 13 and the boat 15 are collectively referred to as an evaporation source. When the boat 15 is heated by the resistance heating power supply 13, the evaporation material 17 is heated through the heat and vapor is generated. The generated vapor reaches and deposits on a film-forming target substrate 18 held in the evaporation dome 14, thereby forming a thin film 19 made of the evaporation material 17. A plurality of boats 15 may be installed in the deposition apparatus 11, which allows the thickness of the same evaporation material to be increased or a plurality of evaporation materials to be formed (not shown).

[0053] In the deposition apparatus 20 of FIG. 2(b), 21 denotes a chamber, 22 denotes an electron gun, 23 denotes an electron gun power supply, 24 denotes an deposition dome, 25 denotes a crucible, 26 denotes a pole piece, and 27 denotes a shutter. The electron gun power supply 23, the electron gun 22, and the crucible 25 are collectively referred to as a deposition source. The electron beam 32 generated from the electron gun 22 is deflected by 150° or more (for example, 180° or 270°) in its traveling direction by the action of a magnetic field formed by the pole piece 26, and is irradiated onto the deposition material 29 contained inside the crucible 25. When the deposition material 29 is irradiated with the electron beam 32, the deposition material 29 is heated and vapor is generated. The generated vapor reaches and deposits on the deposition target substrate 30 held in the deposition dome 24, thereby forming a thin film 31 made of the deposition material 29. A plurality of crucibles 25 are provided on a rotating table, and any crucible can be placed at the electron beam irradiation position by rotating the rotating table (not shown).

[0054] When the electron beam 32 is incident on the deposition material 29 as described above, a part of the irradiated electrons is reflected (backscattered) on the surface of the deposition material 29 due to the input power and material properties, and a certain amount of reflected electrons 33 is emitted. When the reflected electrons 33 reach the substrate 30 after repeatedly reflecting off the inner wall of the deposition apparatus, resin decomposition (embrittlement of the substrate 30) occurs, causing poor adhesion between the substrate 30 and the thin film 31 (the thin film 31 is easily peeled off from the embrittled portion of the substrate 30). Acrylic resin is a material that is particularly susceptible to the influence of the reflected electrons 33 compared to other resins. In order to obtain good adhesion, it is necessary to suppress the influence of the reflected electrons 33, and as a device for capturing the reflected electrons 33, for example, a reflected electron trap has been proposed. The use of a backscattered electron trap is preferable because it can prevent problems such as damage to the substrate and changes in the quality of the thin film caused by the temperature rise of the substrate when the backscattered electrons reach the substrate. Any backscattered electron trap may be used as long as it has the ability to sufficiently capture the backscattered electrons. Examples of the backscattered electron trap include a physical barrier type that attenuates the energy of the backscattered electrons by colliding them multiple times inside an opening provided at the landing point of the backscattered electrons or inside an L-shaped or U-shaped barrier provided in the traveling direction of the backscattered electrons, and a magnetic deflection type that deflects the traveling direction of the backscattered electrons using a magnetic field to capture the backscattered electrons. When using a backscattered electron trap, it is preferable to use a magnetic deflection type because it has a high ability to capture the backscattered electrons, and it is even more preferable to use a combination of a magnetic deflection type and a physical barrier type. The backscattered electron trap 28 in FIG. 2(b) is an example of a magnetic deflection type.

[0055] The general vacuum deposition process for optical thin films involves the following six steps: (1) A substrate is fixed to the deposition dome, and the deposition dome is placed at the top of the chamber. The chamber is evacuated to create a high vacuum. (2) The substrate is heated together with the deposition dome using a halogen heater, sheath heater, etc. At this time, the deposition dome is rotated while heating in order to heat uniformly. (3) With the shutter closed, melting (premelting) of the deposition material is performed. In the case of sublimable materials such as SiO2, however, since they can be sublimated in a granular state, strictly speaking premelting is not necessary, but it is preferable to perform preheating in order to make the transition to the next step (4) smoother (hereinafter, melting and preheating are collectively referred to as premelting). In the case of meltable materials such as Ti3O5, premelting is necessary to prevent bumping (splash) and stabilize the deposition rate. In the case of electron beam heating, reflected electrons may fly out from the gaps in the shutter during premelting and reach the substrate, adversely affecting adhesion, so it is preferable to perform premelting in a short time. (4) When the pressure inside the chamber reaches a specified vacuum pressure (base vacuum pressure) and the substrate temperature stabilizes, the shutter is opened and the atoms and molecules of the deposition material that has become gas are deposited on the substrate surface (evaporation). (5) When a thin film of the desired thickness has been deposited on the substrate, the shutter is closed to terminate deposition. (6) The vacuum is broken, and the deposition dome and the substrate on which the deposited thin film has been formed are removed from the chamber.

[0056] Of the six steps above, steps (1), (2), and (3) are usually performed simultaneously, followed by steps (4), (5), and (6) in that order. Note that heating the substrate in step (2) is optional and does not have to be performed. Furthermore, when forming a multilayer film using different deposition materials, steps (3) to (5) are repeated for the deposition of the second and subsequent materials (hereinafter, the deposition processes for the deposition materials of the second and subsequent materials are denoted as (3)', (4)', and (5)'). In this case, the pre-melting of the deposition materials of the second and subsequent materials (step (3)') may be carried out simultaneously with the pre-melting of the first material (step (3)). By carrying out step (3)' simultaneously with step (3), deposition of the second material (step (4)') can be started immediately after the deposition of the first material (step (4)) is completed, which has the advantage that the vacuum deposition of a multilayer film made of multiple materials can be carried out efficiently.

[0057] In step (4), there are commonly known techniques for forming oxide films by introducing oxygen into the chamber and depositing it while reacting with the atoms and molecules of the deposition material, or for forming a mixture film by simultaneously using multiple deposition materials. In addition, other widely used techniques include ion beam assisted deposition (IAD), which irradiates the surface of the thin film being formed with ions to increase the packing density of the thin film and improve adhesion, and ion plating, which passes gaseous deposition particles through plasma to give them a positive charge, and applies a negative charge to the substrate to attract and volume the gaseous deposition particles, thereby increasing the packing density of the thin film and improving adhesion.

[0058] In the deposition of the undercoat layer P2 of this embodiment, the pressure in the chamber is evacuated to a vacuum in the step (1). -3 It is preferable to evacuate the material so that the pressure is less than 1 Pa. In the heating of the deposition material in steps (3) and (4), a method such as resistance heating, electron beam, high frequency induction, laser, etc. can be appropriately selected depending on the deposition material, the type of substrate, and the target characteristics of the thin film to be produced. In the deposition of the undercoat layer P2 of this embodiment, SiO is used as the deposition material, and it is preferable to use a resistance heating method that does not generate reflected electrons as a heating method from the viewpoint of preventing embrittlement of the lens body P1. In the deposition in step (4), oxygen can be introduced into the chamber to react with the atoms and molecules of the deposition material while depositing the film. In the deposition of the undercoat layer P2 in this embodiment, the pressure in the chamber is set to 1.0×10 -2 It is preferable to control the amount of oxygen introduced so that the pressure is less than 1 Pa.

[0059] <Anti-reflection layer> In the plastic lens P of this embodiment, the antireflection layer P3 is a layer that covers the undercoat layer P2 from the side opposite to the lens body P1. That is, in the plastic lens P of this embodiment, the undercoat layer P2 and the antireflection layer P3 are laminated in this order on the optically effective surface of the lens body P1. The anti-reflection layer P3 has the function of preventing surface reflection in the plastic lens P.

[0060] The antireflection layer P3 is preferably made of a dielectric multilayer film in which high-refractive-index films made of a high-refractive-index material and low-refractive-index films made of a low-refractive-index material having a lower refractive index than the high-refractive-index material are alternately laminated. When the antireflection layer P3 is a dielectric multilayer film having the above-mentioned configuration, it becomes possible to reduce the reflectance for light rays and light beams in a wide range of wavelengths.

[0061] Known materials can be used as the high refractive index material for forming the high refractive index film, and specifically, for example, titanium oxide, zirconium oxide, ditantalum pentoxide, diniobium pentoxide, zinc sulfide, cerium oxide, hafnium oxide, lanthanum titanate, antimony oxide, indium oxide, tin oxide, and mixtures thereof can be used. In addition, materials sold with low oxidation numbers such as Ti2O3 and Ti3O5 or metal materials can be used as deposition materials, and deposition can be performed while introducing oxygen into the chamber to form an oxide film with an arbitrary amount of oxygen introduced. In the anti-reflection layer P3 of this embodiment, it is preferable that the high refractive index film is made of a high refractive index material containing at least one of titanium oxide and zirconium oxide. When the high refractive index film contains at least one of titanium oxide and zirconium oxide, it is preferable in terms of adhesion to the lens body P1 and the undercoat layer P2, ease of material procurement, film stability, and controllability of optical properties in the visible light region. When the antireflection layer P3 includes multiple high refractive index films, the composition of each high refractive index film can be appropriately set according to the design of optical properties. Therefore, the composition of each high refractive index film may be the same or different.

[0062] The refractive index of each high refractive index film at a wavelength of 500 nm is preferably 1.80 or more, more preferably 1.90 or more, and even more preferably 2.00 or more. The refractive index of each high refractive index film is preferably 2.50 or less, more preferably 2.45 or less, and even more preferably 2.40 or less. The refractive index of the high refractive index film can be measured by the method described in the Examples below.

[0063] The thickness (film thickness) of each high refractive index film is preferably 6 nm or more, more preferably 8 nm or more, and even more preferably 10 nm or more. The thickness (film thickness) of each high refractive index film is preferably 150 nm or less, more preferably 125 nm or less, and even more preferably 100 nm or less. When the thickness (film thickness) of each high refractive index film is within this range, the balance of film adhesion, scratch resistance, and controllability of optical properties tends to be good. The thickness (film thickness) of the high refractive index film can be determined, for example, by direct observation of the cross section using an electron microscope, ellipsometry, or spectroscopic reflectometry, and specifically, by the method described in the examples below.

[0064] A known material can be used as the low refractive index material for forming the low refractive index film, and specifically, for example, silicon oxide, magnesium fluoride, yttrium fluoride, thiolite, cryolite, aluminum oxide, and mixtures thereof can be used. In addition, a material sold with a low oxidation number such as SiO or a metal material can be used as a deposition material, and an oxide film containing an arbitrary amount of oxygen can be formed by performing deposition while introducing oxygen into the chamber. In the anti-reflection layer P3 of this embodiment, it is preferable that the low refractive index film contains silicon oxide (however, the refractive index at a wavelength of 500 nm is lower than that of the undercoat layer P2). When the low refractive index film contains the silicon oxide, it is preferable in terms of ease of material procurement, oxidation degree controllability, and film formation stability. In addition, examples of methods for adjusting the refractive index of the low refractive index film containing silicon oxide to be lower than the refractive index of the undercoat layer P2 include a method of using SiO2 as a deposition material for silicon oxide in the antireflection layer P3, and a method of adjusting the oxygen partial pressure (amount of oxygen introduced) when forming the undercoat layer P2 by vacuum deposition, which will be described later. Increasing the oxygen partial pressure (increasing the amount of oxygen introduced) makes the composition closer to SiO2 and the refractive index lower, and decreasing the oxygen partial pressure (reducing the amount of oxygen introduced) makes the composition closer to SiO and the refractive index higher. When the antireflection layer P3 includes multiple low refractive index films, the composition of each low refractive index film can be appropriately set according to the design of optical properties. Therefore, the composition of each low refractive index film may be the same or different.

[0065] The refractive index of each low refractive index film at a wavelength of 500 nm is preferably 1.10 or more, more preferably 1.20 or more, and even more preferably 1.30 or more. The refractive index of each low refractive index film is preferably 1.70 or less, more preferably 1.60 or less, and even more preferably 1.50 or less. The refractive index of the low refractive index film can be measured by the method described in the Examples below.

[0066] The thickness (film thickness) of each low refractive index film is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. The thickness (film thickness) of each low refractive index film is preferably 200 nm or less, more preferably 175 nm or less, and even more preferably 150 nm or less. When the thickness (film thickness) of each low refractive index film is within this range, the balance of film adhesion, scratch resistance, and controllability of optical properties tends to be good. The thickness (film thickness) of the low refractive index film can be determined, for example, by direct observation of the cross section using an electron microscope, ellipsometry, or spectroscopic reflectometry, and specifically, by the method described in the examples below.

[0067] The total thickness (total film thickness) of the antireflection layer P3 is preferably 100 nm or more, more preferably 125 nm or more, and even more preferably 150 nm or more. The total thickness (total film thickness) of the antireflection layer P3 is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. When the total thickness (total film thickness) of the antireflection layer P3 is in this range, the adhesion of the antireflection layer P3 to the lens body P1 and the undercoat layer P2 tends to be good. The total thickness (total film thickness) of the antireflection layer P3 can be determined, for example, by direct observation of the cross section using an electron microscope, ellipsometry, or spectroscopic reflectance analysis, and specifically, by the method described in the examples below.

[0068] The anti-reflection layer P3 of this embodiment can be formed by vacuum deposition, as with the undercoat layer P2. Generally, dry film-forming methods such as vacuum deposition are superior in shape control compared to wet film-forming methods, so the plastic lens P of this embodiment is a plastic lens with excellent shape accuracy that can be used for applications that require advanced surface shape control by forming the undercoat layer P2 and the anti-reflection layer P3 by vacuum deposition. In addition, the plastic lens P of this embodiment can be formed by continuously forming the undercoat layer P2 and the anti-reflection layer P3 by vacuum deposition, so that the number of steps and working time can be reduced, resulting in excellent productivity. In forming the antireflection layer P3 of this embodiment, it is preferable to use resistance heating or an electron beam as a heating method for heating the deposition material in the above-mentioned vacuum deposition steps (3) and (4), and it is particularly preferable to use an electron beam. In the pre-melting of the deposition material in steps (3) and (3)', if resistance heating or an electron beam from an electron gun equipped with a reflected electron trap is used as the heating method from the viewpoint of work efficiency, pre-melting of the deposition material for the anti-reflection layer P3 may be performed simultaneously with the pre-melting of the deposition material for the undercoat layer P2 during the formation of the above-mentioned undercoat layer P2. In addition, in the deposition step (4), the pressure in the chamber is 1.0×10 -3 Pa~5.0×10 -2 It is preferable to control the amount of oxygen introduced so that the pressure is within the range of Pa.

[0069] <Articles using plastic lenses> The plastic lens of the present embodiment can be suitably used for applications such as lenses in household products, office automation equipment, audiovisual equipment, battery-powered electrical components, lighting equipment, and automobile parts.

[0070] One suitable example is a lens for a head mounted display (HMD) for virtual reality (VR). Since a head mounted display is an image display device worn on the head, it is required to be small and lightweight and cause little discomfort when worn. As a means for miniaturization, a method has been proposed in which a lens is combined with a quarter-wave plate and a reflective polarizing plate, etc., and the polarization state of light after passing through the lens is changed to switch between reflection and transmission, thereby making an image make one and a half round trips through a single lens (U.S. Patent No. 6,563,638, JP 2017-21321 A, etc.). The above method has the following mechanism, for example. A quarter-wave plate and a reflective polarizing plate are placed on the back of a lens with a partially reflective coating on the front surface, and the light that enters the lens as circularly polarized light from the front surface is converted to linearly polarized light by the quarter-wave plate after passing through the lens. This linearly polarized light is reflected by the reflective polarizing plate, and is converted again by the quarter-wave plate into the opposite circularly polarized light to the original, which enters the lens from the back surface and reaches the partial reflective coating on the front surface. The light that is reflected by the partial reflective coating and leaves the back surface of the lens is converted by the quarter-wave plate into linearly polarized light with a 90° difference in direction from the original, passes through the reflective polarizing plate, and enters the eye as an image. In this way, a high magnification and wide field of view can be obtained even in a thin optical module.

[0071] If the polarization state changes while passing through the lens, for example, after passing through the lens for the first time, some of the light will pass through the reflective polarizing plate, and images with low and high magnifications will overlap, making it difficult to obtain a clear image, so a lens with low birefringence is required. In addition, the effect on imaging performance caused by changes in lens shape due to changes in humidity during use is also undesirable, so a lens with low moisture absorption and high shape stability in a high temperature and high humidity environment is required. In this regard, the plastic lens of the present embodiment is suitable because it has excellent shape precision and extremely good durability.

[0072] Other examples in which the plastic lens of the present embodiment is preferably used include lenses in household goods, OA equipment, AV equipment, battery-powered electrical components, lighting equipment, and the like, such as lenses for smartphone cameras and tablet PC cameras, lenses used in telephoto cameras (periscope cameras) with curved optical systems; lenses used in VR (virtual reality) / AR (augmented reality) / MR (mixed reality) / SR (substitutional reality) / DR (diminished reality) / XR (cross reality) head-mounted displays, liquid crystal projectors, near-infrared sensors (LiDAR; light detection and ranging), and in particular, small, thin, irregularly shaped optical lenses; lenses for optical communication; lenses, Fresnel lenses, phase plates equipped with microlens arrays, and the like.

[0073] Examples of lenses for automobile parts include lenses used in head-up displays; in-vehicle camera lenses (particularly, front lenses); and the like. Other examples include lenses used in aerial displays, such as the substrates of retroreflective sheets and partially transmissive mirrors, microlens arrays for constructing two-sided corner reflector arrays, and lenses for enlarging or reducing images or correcting image planes or aberrations. EXAMPLES

[0074] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0075] The heat-resistant acrylic resins produced in the production examples were measured and evaluated as follows.

[0076] [Structural Unit Analysis] Unless otherwise noted, 1 H-NMR measurement and 13The structural units of the heat-resistant acrylic resins produced in the Production Examples were identified by C-NMR measurement, and the amounts present were calculated. 1 H-NMR measurement and 13 The measurement conditions for C-NMR measurement are as follows: Measuring equipment: JEOL Ltd. ECZ400 Measurement solvent: CDCl3 or DMSO-d6 ·Measurement temperature: 40℃

[0077] [Molecular weight measurement] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the heat-resistant acrylic resins produced in the Production Examples were measured using the following apparatus and conditions. Measurement equipment: Tosoh Corporation, gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series. Column temperature: 40℃ The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 0.1 g / L of 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Sample: 0.02 g of heat-resistant acrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (Polymer Laboratories; PMMA Calibration Kit MM-10) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the heat-resistant acrylic resin. Based on the calibration curve obtained by measuring the standard sample for the calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the heat-resistant acrylic resin were determined, and the molecular weight distribution (Mw / Mn) was determined using these values.

[0078] [Measurement of glass transition temperature] The glass transition temperature (Tg) (°C) of the heat-resistant acrylic resin was measured in accordance with JIS-K7121. First, from a sample that had been conditioned under standard conditions (23°C, 50% RH) (left at 23°C for one week), test pieces of approximately 10 mg each were cut out at four points (four locations). Next, a differential scanning calorimeter (PerkinElmer Japan Diamond DSC) was used under the condition of a nitrogen gas flow rate of 25 mL / min, where the sample was heated from room temperature (23°C) to 200°C (first heating) at 10°C / min, held at 200°C for 5 minutes to completely melt the sample, then cooled from 200°C to 40°C at 10°C / min, held at 40°C for 5 minutes, and heated again under the above heating conditions (second heating). The intersection (midpoint glass transition temperature) between the step-like change partial curve during the second heating and a straight line equidistant in the vertical direction from each baseline extension line was measured as the glass transition temperature (Tg) (°C). Four measurements were taken per sample, and the arithmetic average (rounded off to the nearest whole number) of the four measurements was taken as the measured value.

[0079] [Vicat softening temperature measurement] The acrylic resin was placed in an injection molding machine (Shibaura Machine Co., Ltd., EC-100SX) and molded into a type 1A dumbbell test piece in accordance with ISO 8257-2. The test piece was conditioned in an oven at a specified temperature for 16 hours, then cooled in a desiccator at 23°C for 1 hour, and the Vicat softening temperature (°C) of the acrylic resin was measured in accordance with ISO 306 B50.

[0080] The raw materials used in the production examples are as follows:

[0081] [Monomer] Methyl methacrylate (MMA): Asahi Kasei Corporation N-Phenylmaleimide (phMI): Nippon Shokubai Co., Ltd. N-Cyclohexylmaleimide (chMI): Nippon Shokubai Co., Ltd. Methyl 2-(hydroxymethyl)acrylate (RHMA): Combi-Blocks Styrene (St): Fujifilm Wako Pure Chemical Industries, Ltd.

[0082] [Organic solvents] Meta-xylene (mXy): Manufactured by Mitsubishi Gas Chemical Co., Ltd. Toluene: Fujifilm Wako Pure Chemical Industries, Ltd. Methyl isobutyrate: manufactured by Kanto Chemical Co., Ltd.

[0083] [Polymerization initiator] 1,1-Di(t-butylperoxy)cyclohexane: NOF Corporation, Perhexa C t-Amyl peroxyisononanoate: Arkema Yoshitomi Co., Ltd., Luperox 570 t-Amylperoxy-2-ethylhexanoate: Arkema Yoshitomi Co., Ltd., Luperox 575

[0084] [Chain transfer agent] n-Octyl mercaptan: Chevron Phillips Chemical Company

[0085] [Other additives, etc.] Stearyl phosphate: Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd. Monomethylamine: Mitsubishi Gas Chemical Company, Inc. Dimethyl carbonate: Fujifilm Wako Pure Chemical Industries, Ltd. Triethylamine: Fujifilm Wako Pure Chemical Industries, Ltd. Pd / C: NE Chemcat Corporation Rikemal H-100: manufactured by Riken Vitamin Co., Ltd.

[0086] (Production Example 1: Heat-resistant acrylic resin A) 358.6 kg of methyl methacrylate (hereinafter referred to as MMA), 29.4 kg of N-phenylmaleimide (hereinafter referred to as phMI), 67.7 kg of N-cyclohexylmaleimide (hereinafter referred to as chMI), 0.77 kg of n-octyl mercaptan as a chain transfer agent, and 224.3 kg of meta-xylene (hereinafter referred to as mXy) ​​were weighed out and added to a 1.25 m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 88.0 kg of MMA, 6.3 kg of phMI, and 142.4 kg of mXy were weighed and added to Tank 1 with stirring to obtain a mixed monomer solution for additional addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and the liquid in Tank 1 was bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 115°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.470 kg of 1,1-di(t-butylperoxy)cyclohexane in 1.905 kg of mXy at a rate of 1.0 kg / hour while stirring at 50 rpm. During the polymerization, the solution temperature in the reactor was controlled at 115±2° C. by adjusting the temperature with a jacket. After 30 minutes from the start of the polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour. In addition, starting from 1 hour after the start of polymerization, the additional mixed monomer solution was added in its entirety from Tank 1 at a constant rate over a period of 4 hours. Furthermore, the addition rate of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of polymerization, and the addition was stopped 5 hours after the start of polymerization. After 12 hours had elapsed since the start of the polymerization, a polymer solution containing a heat-resistant acrylic resin having a ring structure in its structure (main chain) was obtained, and the polymerization was terminated. This polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10 to 15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a heat-resistant acrylic resin A. The composition of the obtained pellets was confirmed to be 81.0 mass%, 6.6 mass%, and 12.4 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, in the copolymer, and the weight average molecular weight was 108,000, Mw / Mn was 2.04, the glass transition temperature was 134°C, and the Vicat softening temperature was 124°C.

[0087] (Production Example 2: Heat-resistant acrylic resin B) A glutarimidated resin was produced using a 15 mm diameter intermeshing co-rotating twin screw extruder using a methyl methacrylate-styrene copolymer (styrene amount 8 mass%) with a molecular weight of 100,000 as the raw resin and monomethylamine as the imidizing agent. The temperature setting of each temperature control zone was 230 to 250°C, and the screw speed was 150 rpm. Methyl methacrylate-styrene copolymer (hereinafter also referred to as "MS resin") was supplied at 2 kg / hr, and the resin was melted and filled by the kneading block, and then 8 parts by mass of monomethylamine was injected from the nozzle relative to the resin. A reverse flight was inserted at the end of the reaction zone to fill it with resin. The by-products and excess monomethylamine after the reaction were removed by reducing the pressure at the vent port to -0.092 MPa. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain a glutarimidated MS resin intermediate (1). Next, a 15 mm diameter co-rotating intermeshing twin screw extruder was set with the temperature of each temperature control zone set to 230°C and the screw speed set to 150 rpm, and the glutarimidated MS resin intermediate (1) obtained from the hopper was fed at 1 kg / hr. The resin was melted and filled by the kneading block, and then a mixture of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected into the resin from the nozzle to reduce the carboxyl groups in the resin. A reverse flight was placed at the end of the reaction zone to fill the resin. The by-products and excess dimethyl carbonate after the reaction were removed by reducing the pressure at the vent port to -0.092 MPa. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain glutarimidated MS resin intermediate (2). Furthermore, the glutarimidated MS resin intermediate (2) was fed into a 15 mm diameter co-rotating intermeshing twin screw extruder with the temperature control zones set at 230°C, the screw speed at 150 rpm, and the feed rate at 1 kg / hr. The pressure at the vent port was reduced to -0.095 MPa, and volatile matters such as unreacted auxiliary materials were removed again. The devolatilized imide resin that came out as strands from the die at the extruder outlet was cooled in a water tank and pelletized in a pelletizer to obtain heat-resistant acrylic resin B (glutarimidated MS resin). The heat-resistant acrylic resin B had a weight average molecular weight of 85,000, an Mw / Mn of 1.8, the contents of the monomer units in the copolymer were 8 mass% styrene units, 82 mass% MMA units, and 10 mass% glutarimide units, the glass transition temperature was 128°C, and the Vicat softening temperature was 120°C.

[0088] (Production Example 3: Heat-resistant acrylic resin C) A reaction vessel equipped with a stirrer, a temperature sensor, a cooling pipe, a nitrogen inlet pipe, and a dropping pump was charged with 5.40 parts by mass of methyl 2-(hydroxymethyl)acrylate (hereinafter referred to as RHMA), 37.6 parts by mass of methyl methacrylate (hereinafter referred to as MMA), 0.450 parts by mass of styrene (hereinafter referred to as St), and 90.0 parts by mass of toluene, and the temperature was raised to 105°C while passing nitrogen through. As an initial initiator, a solution consisting of 3.63 parts by mass of toluene and 0.245 parts by mass of t-amyl peroxy isononanoate was dropped over 9 minutes while solution polymerization was carried out at 105 ° C. to 110 ° C. Then, 11 minutes later, a solution consisting of 4.42 parts by mass of toluene and 0.298 parts by mass of t-amyl peroxy isononanoate was dropped over 180 minutes as a dropping initiator. In addition, simultaneously with the dropping initiator addition, a solution consisting of 6.6 parts by mass of RHMA, 45.9 parts by mass of MMA, and 4.05 parts by mass of St was dropped over 180 minutes while solution polymerization was carried out at 105 ° C. to 110 ° C., and further aging was carried out over 100 minutes. To the obtained polymerization solution, a solution consisting of 1.20 parts by mass of toluene and 0.0750 parts by mass of stearyl phosphate was added as a catalyst (cyclization catalyst) for the cyclization condensation reaction, and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed for 1.5 hours under reflux at approximately 90°C to 110°C. Next, the obtained polymerization solution was passed through a multi-tube heat exchanger maintained at 220°C to complete the cyclization condensation reaction, and then introduced into a vent-type screw twin-screw extruder (L / D=52) equipped with a leaf disk-type polymer filter (filtration accuracy 5μm) at the tip at a processing rate of 90 parts by mass / hour in terms of resin amount to devolatilize the polymerization solution. The number of rear vents of the vent-type screw twin-screw extruder used was 1, and the number of fore vents was 4 (referred to as the first, second, third, and fourth vents from the upstream side), the barrel temperature was 220°C, and the degree of vacuum was 13.3 to 400hPa (10 to 300mmHg). During devolatilization, ion-exchanged water was introduced from behind the first, second, and third vents at an introduction rate of 1.3 parts by mass / hour. The weight average molecular weight of the obtained heat-resistant acrylic resin C was 102,000, Mw / Mn was 2.3, the glass transition temperature was 125°C, the Vicat softening temperature was 116°C, and the proportions of MMA units, styrene units, lactone ring structures and RHMA units in the copolymer were 76.8% by mass, 4.6% by mass, 16.9% by mass and 1.7% by mass, respectively.

[0089] (Production Example 4: Heat-resistant acrylic resin D) A monomer composition consisting of 75.09 parts by mass of MMA, 26.04 parts by mass of styrene, and 0.46 parts by mass of t-amylperoxy-2-ethylhexanoate as a polymerization initiator was continuously fed at 1 kg / h to a 10 L complete mixing tank with a helical ribbon blade, and continuous polymerization was performed at an average residence time of 2.5 hours and a polymerization temperature of 150 ° C. The liquid was continuously withdrawn from the bottom so that the liquid level in the polymerization tank was constant, and was fed to a concentrating device consisting of a tubular heat exchanger and a vaporization tank for devolatilization. The vacuum degree of the vaporization tank was set to 10 to 15 Torr. The resin that flowed down the vaporization tank was discharged with a screw pump, extruded from a strand die, pelletized after water cooling, and introduced into a desolvation device to obtain a pellet-shaped methyl methacrylate-styrene copolymer. This copolymer was dissolved in methyl isobutyrate to prepare a 10% by mass methyl isobutyrate solution. 500 parts by mass of this 10% by mass methyl isobutyrate solution of the copolymer and 1 part by mass of 10% by mass Pd / C as a hydrogenation catalyst were charged into a 1000 mL autoclave apparatus, and the mixture was maintained at 200°C and a hydrogen pressure of 9 MPa for 15 hours to hydrogenate the aromatic double bonds of the styrene moiety of the copolymer. The hydrogenation catalyst was removed by a filter, and 0.04 parts by mass of Rikemar H-100 was added to and mixed with the polymer solution, and the mixture was fed to a concentrator consisting of a tubular heat exchanger and a vaporization tank for devolatilization. The vacuum degree of the vaporization tank was set to 10 to 15 Torr. The resin that flowed down the vaporization tank was discharged by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a heat-resistant acrylic resin D. The composition of the obtained pellets was confirmed to be 73.2% by mass and 26.8% by mass of structural units derived from MMA and vinylcyclohexane monomers, respectively. The weight average molecular weight was 148,000, Mw / Mn was 2.0, the glass transition temperature was 118°C, and the Vicat softening temperature was 112°C.

[0090] The methods for measuring and evaluating each layer formed in the examples and comparative examples are as follows.

[0091] [Refractive Index] The refractive index at a wavelength of 500 nm of each layer formed in the examples and comparative examples was determined by a spectral reflectance method after previously forming a single layer on a glass substrate (optical glass B270i) under the same film formation conditions and measuring the spectral reflectance using an ultraviolet-visible-near infrared spectrophotometer (UH4150, manufactured by Hitachi High-Tech Corporation).

[0092] [Thickness of each layer (film thickness)] The thickness (film thickness) of each layer formed in the examples and comparative examples was measured using a spectroscopic ellipsometer (UVISEL2, manufactured by Horiba, Ltd.) Note that, for the calculation of the film thickness, data of a sample in which a single layer was formed on a glass substrate (optical glass B270i) under the same film formation conditions was used.

[0093] [Example 1] (Lens molding) Using the heat-resistant acrylic resin A obtained in Production Example 1, injection molding was performed using an injection molding machine (FANUC Corporation, S-2000i50B) to obtain a plano-convex lens molded product (lens body) with an optical axis thickness of 3.2 mm and an effective diameter of φ41 mm. As a result, one surface including the optical axis has an aspheric shape with a radius of curvature R93.5 mm, a conic constant k of -1.12452, and no even-order constants are set. In addition, the other surface including the optical axis has a planar shape with a radius of curvature ∞. The cylinder temperature was set to Tg+135℃ of the heat-resistant acrylic resin A used, and the mold temperature was set to Tg-15℃ of the heat-resistant acrylic resin A used. The first stage of the holding pressure was set to 60MPa for 4 seconds, and then the second stage of the holding pressure was set to 40MPa for 3 seconds in order to relieve the stress distortion inside the molded product. The injection speed was set to 10mm / s. (Deposition of undercoat layer and anti-reflection layer) An undercoat layer and an anti-reflection layer were formed on the flat surface side of the above-mentioned lens molded product by a vacuum deposition method using a vacuum deposition apparatus (manufactured by Showa Shinku Co., Ltd., SAPIO SGC-1300). The lens molded product was placed in the vacuum deposition device, and the vacuum chamber was heated to 1.5 x 10 -3The chamber was evacuated to a pressure of 1.8×10 Pa. Next, the SiO granules packed in the molybdenum boat were heated and sublimated by resistance heating to form an undercoat layer with a thickness of 320 nm. During the film formation, oxygen gas was used as a reactive gas at a total pressure of 1.8×10 -3 The deposition material used in the next step of forming the antireflection layer was not pre-melted before or during the formation of the undercoat layer. Next, the Ti3O5 granules filled in the copper liner were heated, melted, and vaporized by an electron gun, and a TiO2 layer with a high refractive index was formed by electron beam deposition. During the film formation, oxygen gas was used as a reactive gas at a total pressure of 1.3 × 10 -2 The electron beam was introduced so that the pressure was adjusted to Pa, and the film was formed without heating the target (molded lens + undercoat layer). In addition, the electron beam heating of the deposition material, Ti3O5, was started with the shutter closed, and the deposition material was pre-melted, and then the shutter was opened to form the film. Next, the SiO2 granules filled in the copper liner were heated and sublimated by an electron gun, and the SiO2 layer, which is a low refractive index layer, was formed by electron beam deposition. During the film formation, oxygen gas was used as a reactive gas at a total pressure of 1.3 × 10 -2 The electron beam was introduced so that the pressure was adjusted to Pa, and the film was formed without heating the target (lens molded product + undercoat layer + TiO2 layer). In addition, the electron beam heating of the deposition material SiO2 was started with the shutter closed, and the deposition material was pre-melted, and then the shutter was opened to form the film. The above-mentioned TiO2 layer and SiO2 layer were alternately formed three times to form an anti-reflection film having the structure shown in Table 1, thereby obtaining a plastic lens. The electron gun used to heat the deposition material was not equipped with a reflected electron trap. In addition, the deposition material to be used in the next step of depositing the SiO2 layer was not pre-melted before or during the deposition of the TiO2 layer, and similarly, the deposition material to be used in the next step of depositing the TiO2 layer was not pre-melted before or during the deposition of the SiO2 layer.

[0094] [Example 2] A plastic lens provided with an undercoat layer and an anti-reflection layer was produced in the same manner as in Example 1, except that heat-resistant acrylic resin B was used instead of heat-resistant acrylic resin A as the heat-resistant acrylic resin.

[0095] [Example 3] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that heat-resistant acrylic resin C was used instead of heat-resistant acrylic resin A as the heat-resistant acrylic resin.

[0096] [Example 4] A plastic lens provided with an undercoat layer and an anti-reflection layer was produced in the same manner as in Example 1, except that heat-resistant acrylic resin D was used instead of heat-resistant acrylic resin A as the heat-resistant acrylic resin.

[0097] [Example 5] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the undercoat layer was formed to a thickness of 450 nm.

[0098] [Example 6] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the undercoat layer was formed to a thickness of 610 nm.

[0099] [Example 7] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the undercoat layer was formed to a thickness of 900 nm.

[0100] [Example 8] An electron gun equipped with a reflected electron trap was used as the electron gun for heating the deposition material, and the rest was the same as in Example 1 to produce a plastic lens provided with an undercoat layer and an antireflection layer.

[0101] [Example 9] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that an electron gun equipped with a reflected electron trap was used as the electron gun for heating the deposition material, and premelting of the deposition material to be used in the subsequent process of forming the antireflection layer was performed before and during the formation of the undercoat layer.

[0102] [Comparative Example 1] When forming the undercoat layer, oxygen gas was used at a total pressure of 1.4 × 10 -2 A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the above-mentioned components were introduced so as to obtain a refractive index of 1.0 Pa.

[0103] [Comparative Example 2] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the undercoat layer was formed to a thickness of 250 nm.

[0104] [Comparative Example 3] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that the undercoat layer was formed to a thickness of 100 nm.

[0105] [Comparative Example 4] A plastic lens provided with an undercoat layer and an antireflection layer was produced in the same manner as in Example 1, except that an undercoat layer was formed to a thickness of 100 nm and an electron gun equipped with a reflected electron trap was used as the electron gun for heating the deposition material.

[0106] [Comparative Example 5] A plastic lens having an undercoat layer and an anti-reflection layer was produced in the same manner as in Example 1, except that an acrylic resin without heat resistance (Delpet 80N, manufactured by Asahi Kasei Corporation, Vicat softening temperature 109°C) was used instead of the heat-resistant acrylic resin A.

[0107] The plastic lenses produced in the examples and comparative examples were measured and evaluated as follows.

[0108] (Durability evaluation) (1) Initial adhesion In order to evaluate the coating adhesion of the plastic lenses obtained in the examples and comparative examples, a cross-cut test was performed according to JIS K 5600-5-6. 25 1mm x 1mm squares were made on the flat surface of the plastic lens using a multi-blade cutting tool, cellophane tape ("LP-24" manufactured by Nichiban Co., Ltd.) was applied on the squares, and the tape was quickly removed, and the surface condition of the cross-cut part was observed to see whether the film (undercoat layer and anti-reflection layer) had peeled off. The results were classified as follows, with classification 0 or 1 being A (good), classification 2 being B (practical), and classifications 3 to 5 being C (bad). (classification) 0: The edges of the cut are completely smooth and there are no peeling marks on any of the squares. 1: There is a small amount of peeling of the film at the intersection of the cuts. The percentage of peeling at the cross-cut portion does not clearly exceed 5% of the total area of ​​the cross-cut portion, taken as 100%. 2: The membrane has small separations along the edges of the cuts and / or at the intersections. The percentage of separations at the cross-cuts is clearly greater than 5% but not greater than 15% of the total cross-cut area (100%). 3: The membrane is partially or completely peeled along the edges of the cuts and / or partially or completely peeled in several squares. The percentage of peeling in the cross-cut area is clearly more than 15% but not more than 35% of the total cross-cut area (100%). 4: The membrane has peeled partially or completely along the edges of the cuts and / or has peeled partially or completely in several squares. The percentage of peeling in the cross-cut area is clearly more than 35% but not more than 65% of the total cross-cut area (100%). 5: Any degree of peeling that cannot be classified as category 4.

[0109] (2) Humidity and heat test A wet heat test was carried out using the plastic lenses obtained in the examples and comparative examples. The plastic lenses were placed in a thermohygrostat (PL-4KP manufactured by Espec Corporation) set at 85°C and 85% RH, and were kept in an 85°C, 85% RH environment for 200 hours. Thereafter, the plastic lenses were removed from the thermohygrostat and kept in a thermostatic chamber at 23°C and 50% RH for 24 hours. (2-1) Appearance change after wet heat test After the wet heat test, the lens surface of the plastic lens was visually observed to determine whether or not cracks had occurred. (2-2) Adhesion after wet heat test After the wet heat test, the plastic lenses were evaluated for adhesion to the films (undercoat layer and antireflection layer) using the same evaluation method as for the initial adhesion in (1).

[0110] The measurement and evaluation results are shown in Table 1. [Table 1] [Industrial Applicability]

[0111] The plastic lens of the present invention has excellent productivity and excellent durability, and can therefore be suitably used for applications such as lenses in household products, office automation equipment, audiovisual equipment, battery-powered electrical equipment parts, lighting equipment, and automobile parts. Examples of lenses used in household goods, office automation equipment, audio-visual equipment, battery electrical components, lighting equipment, and the like include lenses for smartphone cameras and tablet PC cameras, lenses used in telephoto cameras (periscope cameras) with curved optical systems; lenses used in VR (virtual reality) / AR (augmented reality) / MR (mixed reality) / SR (alternative reality) / DR (reduced reality) / XR (cross reality) head-mounted displays, liquid crystal projectors, near-infrared sensors (LiDAR), and in particular, small, thin, non-uniformly shaped optical lenses; lenses for optical communications; lenses, Fresnel lenses, phase plates equipped with microlens arrays, and the like. Examples of lenses for automobile parts include lenses used in head-up displays; in-vehicle camera lenses (particularly, front lenses); and the like. Other examples include lenses used in aerial displays, such as the substrates of retroreflective sheets and partially transmissive mirrors, microlens arrays for constructing two-sided corner reflector arrays, and lenses for enlarging or reducing images or correcting image planes or aberrations. [Explanation of symbols]

[0112] P Plastic Lens P1 lens body P2 Undercoat layer P3 Anti-reflection layer Sa, Sb Optically effective surface Z optical axis 11 Vapor deposition equipment 12 Chambers 13 Resistance heating power supply 14 Evaporation Dome 15. Boat 16 Shutter 17 Evaporation materials 18. Substrate for film formation 19 Thin Film 20 Vapor deposition equipment 21 Chamber 22 Electron Gun 23 Electron gun power supply 24 Evaporation Dome 25 Crucible 26 Pole Piece 27 Shutter 28 Reflected electron trap 29 Evaporation materials 30 Substrate for film formation 31 Thin Film 32 Electron Beam 33 Backscattered electron

Claims

1. A plastic lens comprising a lens body, an undercoat layer covering at least one optically effective surface of the lens body, and an anti-reflection layer covering the undercoat layer from the side opposite to the lens body, The lens body includes a heat-resistant acrylic resin, The undercoat layer is made of silicon oxide (SiO). x (1<x<2), The refractive index of the undercoat layer at a wavelength of 500 nm is 1.60 or more and 1.70 or less, The thickness of the undercoat layer is more than 300 nm and less than 1000 nm. A plastic lens characterized by:

2. The plastic lens according to claim 1 , wherein the undercoat layer has a thickness of more than 300 nm and not more than 800 nm.

3. the antireflection layer is formed by alternately laminating high refractive index films made of a high refractive index material and low refractive index films made of a low refractive index material, the high refractive index material is at least one of titanium oxide and zirconium oxide, 3. The plastic lens according to claim 1, wherein the low refractive index material is silicon oxide having a refractive index at a wavelength of 500 nm lower than that of the undercoat layer.

4. 3. The plastic lens according to claim 1, wherein the heat-resistant acrylic resin has a glass transition temperature of 116° C. or higher.

5. The heat-resistant acrylic resin contains a structural unit having a ring structure in the structure, the structural unit having a ring structure includes at least one selected from the group consisting of a cyclic imide structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit, and a lactone ring structural unit, 3. The plastic lens according to claim 1, wherein the proportion of the structural unit having a ring structure in the heat-resistant acrylic resin is 15% by mass or more.

Citation Information

Patent Citations

  • Antireflection film of optical parts made of synthetic resin

    JP1994273601A

  • Plastic lens, lens unit and method for producing plastic lens

    WO2023074597A1

Cited By

  • Method of fabricating plastic lens

    JP2025157144A

  • Method of fabricating plastic lens

    JP2025157145A

  • Manufacturing method of plastic lenses

    JP7866097B2

  • Manufacturing method of plastic lenses

    JP7866098B2